PWE-090 Outcomes of Patients with Ulcerative Colitis who are Azathioprine Tolerant and Azathioprine Intolerant. (4th June 2013) - Lee, L; Syed, A; Macfaul, G; Lanzon-Miller, S
Abstract : Introduction: Azathioprine therapy is an immunosuppressive drug that is widely used in the management of ulcerative colitis. 20% of patients with normal TPMT are not able to tolerate the drug and 30% do not respond [1]. For patients who are intolerant to azathioprine, other medicines have been proposed and these include methotrexate, mercaptopurine and infliximab. Methods: A cross sectional study was performed using the Milton Keynes Hospital IBD database to compare patients were azathioprine intolerant and those that were azathioprine tolerant. A descriptive analysis of clinical features and outcomes of these two groups was performed. Disease activity scores were based on the montreal classification ranging from S0 (clinical remission) to S3 (severe disease). Results: 98 patients were recruited of which 32.7% were intolerant to azathioprine. The median age of azathioprine intolerant patients was 47.5 years and 30.3% were male. In the azathioprine tolerant cohort, the median age was 46 years and 53.0% were male. Azathioprine was not tolerated due to deranged liver function tests in 43.3%, gastrointestinal symptoms of nausea/vomiting in 23.3%, cutaneous side effects in 10.0%, migraines in 6.7% and infections in 3.3%. Conclusion: Azathioprine is a drug that is not tolerated in nearly a third of Ulcerative Colitis patients and this effect demonstrated a sex bias towards females. The most likely reason for azathioprine intolerance was deranged liver function tests, however, intolerable gastrointestinal symptoms are noted. The intolerance of azathioprine is not a prognostic marker that patients will be more likely to undergo colectomy or that their ulcerative colitis will become extensive. However, there is evidence that compared to azathioprine tolerant patients, for every 100 who are intolerant, 8 less will be in remission and 6 will have more severe disease. Finally, we note that prolonged use of low-dose steroids in modern practise is utilised rarely and it is feasible that this trend may lead to increased symptoms at a population level. Disclosure of Interest: None Declared. References: M. Wahed, J. R. Louis-Auguste, L. M. Baxter, J. K. Limdi, S. A. Mccartney, J. O. Lindsay, and S. L. Bloom, "Efficacy of methotrexate in Crohn's disease and ulcerative colitis patients unresponsive or intolerant to azathioprine/mercaptopurine, " Alimentary Pharmacology & Therapeutic s, vol. 30, no. 6, pp. 614–620, 2009.